Considerations Toward how Movements Learn from and Educate each Other: Global Histories from Below from a Pedagogical Standpoint - John Holst; Maria A Vetter; Mai Atta; Kamil Gerónimo-López; Javier Campos-Martínez (Adult Education Research Conference, 2023)
Using the concept of world histories from below, we present research on the global flow of ideas, protest repertoires, and pedagogies across three social movements in three countries.
Keywords: Social Movement Learning; World Histories from Below; Social Movement Theory